Effectiveness of Deep Breathing Relaxation Combined Guided Imagery with Music on Pain Scale in Patients After Caesarean Section - Purnamasari, Ira; Sumarliyah, Eni; Aisyah, Siti; Firman, Firman; Nasrullah, Dede (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Caesarean Section (CS) is a surgical procedure to remove the fetus through an incision in the abdominal wall and uterine wall. A common problem in post-CS patients is pain. Deep breathing relaxation and guided imagery are non-pharmacological techniques to reduce pain. The purpose of this study was to determine the effect of deep breathing relaxation techniques combined with guided imagery accompanied by music on the pain scale in post-CS patients. The methods of this study used a pre-experimental design with one group pre-test post-test design. The sampling technique used purposive sampling where a sample of 32 respondents was obtained. The data analysis technique used a paired sample t-test program with a significance level of α = 0.05. The results of this study are the pain scale before the intervention was moderate pain (56.3%) and severe pain (43.7%). Meanwhile, the pain scale after the intervention was mild pain (40.6%), moderate pain (50%), and severe pain (9.4%) with a ρ value of 0.001 < α = 0.05. The conclusion of this study is deep breathing relaxation techniques combined with guided imagery and music can reduce pain intensity in post-CS patients. These techniques can be implemented according to standard operating procedures (SOPs) so that nurses don't focus solely on pharmacological therapy.